Agreement with COVID-19 Conspiracy Theories Has Poor Temporal Stability - Pisl, Vojtech; Volavka, Jan; Kavalirova, Gabriela; Vevera, Jan (Disaster medicine and public health preparedness, 2024)
Low temporal stability may complicate the interpretation of survey measures of conspiracy theories (CTs). Current study examines the stability of endorsement of CTs on a popular set of items addressing COVID-19-related CTs. An online survey tapping two CTs about COVID-19 was administered to 179 students of general medicine. The same items were presented twice in March 2022 and once in May 2022. The mean endorsement of the CTs did not differ between March and May. The correlation between answers provided in March and May was low (.5 < r < .7). Most of those reporting agreement with CTs in March reported disagreement in May. Conspiracy believers' responses did not change between two measurements in March but were different in May, suggesting that the low temporal stability was due to situational factors rather than erroneous or random answers. Poor temporal stability of responses endorsing CTs may problematize interpretation of survey data. Respondents' endorsement of CTs may be affected by situational factors, inflating agreement with CTs, and correlations with other survey-based measures.
Keywords: průzkumy a dotazníky; mužské pohlaví; ženské pohlaví; COVID-19; dospělí; Humans; Adult; Female; Male; Surveys and Questionnaires; lidé; SARS-CoV-2